THE EFFECT OF DIFFERENT CONCENTRATIONS OF ETHEPHON AND LACK OF IRRIGATION DURING THE PLANT GROWTH STAGES ON THE CHARACTERISTICS OF GROWTH AND YIELD OF SAFFLOWER PLANTS - Nisreen Aqeel Hussain1 and Shaimaa Ibrahiem Al-Refai2 (Chelonian Research Foundation, 2023)
The experiment was conducted to study the effect of ethephon and moisture stress at different growth stages on the yield, its components, and the efficiency of water consumption of safflower (Gilla) variety. The experiment was carried out during the winter season 2021-2022 on 11/24/2021 in the Boulatif area, which is 3 km from the governorate center in A farmer's fields in Muthanna Governorate. It was implemented using a split-plot design with three replications, where the first factor included four levels (full irrigation - dropping irrigation at branching - dropping irrigation at the flower bud - dropping irrigation at the filling period), which was symbolized by the symbol. I 1, I 2, I 3, I 4 The second factor: Spraying with ethephon at five levels of 2000-1500-1000-500 - 0 mg/L, with a plant density of 40,000 plants/ha. The results of the experiment showed the superiority of the treatment. The ethephon spray treatment at a concentration of 1500 mg L-1 was superior by giving it the lowest average plant height (107.6) cm and the weight of 500 seeds was (19.31) grams. It was superior by giving it the highest number of branches per plant (267.7) branch plant-1, and the weight of the plant. The dry amounted to (18.33) tons ha-1, the number of heads per plant (213.7) per plant head-1 for the first season, and the number of seeds per head (41.05) per seed head-1, in addition to giving it the highest percentage of stem diameter of (16.95). The lack of irrigation in the different stages of growth did not significantly affect most of the characteristics of the study, as the lack of irrigation treatments did not differ significantly among themselves in the following characteristics (plant height, number of branches, number of leaves, total chlorophyll content, number of heads, number of seeds per head). The effect of the interaction between the ethephon spraying treatments and the lack of irrigation treatments was significant in most of the characteristics of the study, as the combination was superior to the lack of irrigation during branching It gave the highest averages for the mentioned characteristics, which amounted to (282.7 and 247 plant heads-1), (56.67 and 58.33 seeds per head-1), (133.3 and 161.7 g plant-1), (5.333)m Keywords: safflower, ethephon, water consumption